Coupling of alkaline precipitation and alkali-activated hydrogen peroxide oxidation for reuse of cotton pulp black liquor. (15th March 2021) - Liu, Xiaochen; Lu, Jun; Ayele, Befkadu A.; Li, Die; Chen, Quanyuan
Abstract: The cotton pulp black liquor (CPBL) is high alkalinity wastewater generated in the production of cotton pulp dreg. In the present work, CPBL was treated by a coupling process of alkaline precipitation and alkali-activated hydrogen peroxide (H2 O2 ) oxidation to remove colorants, so that the water and alkali can be reused in cotton linters cooking for cleaner production of cotton pulp dreg. The influence of main operating parameters of alkaline precipitation and alkali-activated H2 O2 oxidation was investigated. The reactive oxygen species (ROS) tests in alkali-activated H2 O2 combined with analyses of degradation products were conducted to explore the possible reaction mechanism. Experimental results showed that alkaline precipitation was more effective compared to traditional acid precipitation. The removal efficiencies of COD, UV254 and color were 30.83%, 40.69% and 65.21%, when 13 g L −1 CaCl2 was added. Removal efficiencies of UV254 of 30.22% and color of 80.78% can be achieved for the alkali-activated H2 O2 process (H2 O2 dosage of 30 mmol L −1, 2 h reaction time, and temperature 60 °C). Consequently, total removals of UV254, lignin and color were 61.4%, 67.8% and 92.79% in the integrated process. The quality of the effluent after treatment satisfied requirements of recycling for cotton pulp dreg production. It was found that superoxide radical (O2 −· ) was the dominant ROS and hydroxyl ion (OH − ) was mainly responsible for activation of H2 O2 in the oxidation process. Graphical abstract: Image 1 Highlights: Alkaline precipitation was more effective than acid precipitation in CPBL treatment. OH − was main activator of H2 O2 for the oxidation of lignin and hemicellulose. O2 −· and HO2 − played a crucial role in the alkali-activated H2 O2 oxidation process. Treated CPBL can be reuse in the cooking process of cotton pulp dreg production.